TANTANGAN REGULASI 4.0 DI ERA DISRUPSI DIGITAL DALAM PERSPEKTIF SOSIOLOGI HUKUM - Ivan, Muhammad (Jurnal Inovasi Daerah, 2024)
This research aims to show the challenges of regulation 4.0 in the era of disruption and provide a greater understanding of how governments can respond and utilize new technology in the field of regulation. A qualified regulation is not only simple and orderly but also requires evaluation and visibility on both existing and future regulations. In the digital age, which emphasizes efficiency and productivity, the spirit of regulation must be able to keep pace with the speed of various disruptions that might occur in the future. Regulatory changes that sooner or later will affect social and cultural shifting, that significantly change the norms and values in society, the solution is need is perspective sociology of law Indeed. This research is a qualitative research, while data collection is collected through a literature study in the form of books; article; and online publication. The results showed that in producing qualified regulations will be largely determined by the resources and technological capabilities of the government. In addition, the education sector, collaboration between institutions, and community trust have a significant impact in planning, implementing and evaluating regulations